Construção de roadmaps para análise das perspectivas da cadeia produtiva de briquetes e pellets de biomassa dos resíduos agrícolas para geração de bioenergia - Ribeiro, Guilherme Fernando (2024)
This research was concerned with discussing the issue of renewable energy sources. Given the environmental problems caused by fossil fuels, it is essential to find new sustainable energy sources. Among the various justifications for carrying out this research, it is worth mentioning that, as stated in the National Energy Plan (PNE), prepared by the Ministry of Mines and Energy, through the Secretariat of Planning and Energy Development, and catalogued by the Energy Research Company (EPE), the issue of agricultural waste should be considered a path of study to support the design of the strategy of decision-makers and stakeholders involved in relation to the expansion of the energy sector. Thus, a study was carried out with the objective of developing roadmaps for the production chain of briquettes and biomass pellets from agricultural waste for the generation of bioenergy. The Delphi method was used, which seeks to obtain a consensus agreement among experts on the proposed topic, and was carried out by preparing two questionnaires: rural producers and industries - which were validated in four areas: Portuguese language, psychology, statistics and experts, in addition to the application of Cronbach's alpha coefficient (which resulted in a global coefficient with optimal internal consistency for both questionnaires), which demonstrates their reliability and consistency. In order to contribute to the treatment of the objective in question, an approach based on the principles of the Technology Roadmapping Method (TRM) was used. The analysis of the results was carried out in a way that contemplated all the stages of a production chain, that is, according to the agribusiness transformation model (before, inside and after the farm gate), and also according to the industrial transformation model (input, processing and output), that is, it contemplated aspects related to the field (collection of agricultural waste) and related to the industry (production of briquettes and pellets). The research revealed significant initial resistance from rural producers to the use of agricultural waste for the production of briquettes and pellets for bioenergy, in contrast to the interest of industries. The main barriers include: technological development and adaptation of agricultural machinery; financial incentives for rural producers; economic viability; and concerns about soil characteristics. It is strongly believed that the use of agricultural waste for the production of briquettes and pellets has immense potential that is still unexplored. Adopting the removal of agricultural waste from the field will require continuous efforts and technological innovation. The roadmaps developed act as a strategic guide for balanced decision-making that is adaptable to specificities. They map opportunities and challenges in the use of agricultural waste for the generation of bioenergy, suggest approaches to overcome these challenges and take advantage of opportunities in the production chain of briquettes and pellets, and point out solutions to the main barriers, encouraging the adoption of this practice by the actors involved.